Pengaruh Rasio Keuangan Terhadap Manajemen Laba Pada Perusahaan Real Estate dan Properti di BEI Periode 2017-2022 - Koesmandoyo, Jovandra Gabriel; Susilowati, Clara (Value : Jurnal Manajemen dan Akuntansi, 2024)
This study addresses important issues related to earnings management in real estate and property companies amid the economic challenges posed by the Covid-19 pandemic. The research examines how profitability, liquidity, leverage, activity, and growth ratios influence earnings management in this crisis context. The objective of this study is to determine the impact of these financial ratios on earnings management in companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2022 period. Employing a quantitative approach with secondary data from 25 companies, the analysis was conducted through classical assumption tests and F-tests as well as t-tests using SPSS software. The results indicate that these ratios do not have a significant impact on earnings management. This finding is intriguing because these factors are typically considered influential in earnings management practices. However, in the context of the pandemic, external factors such as economic instability and government policies are more dominant, rendering internal financial ratios less relevant.